Leksikon Kepisangan Bahasa Bali di Kabupaten Karangasem: Kajian Morfo-Sintaksis - Suryati, Ni Made; Duana Sutika, I Nyoman; Suastini, Ni Nyoman (Humanis; Vol 29 No 2 (2025)DO - 10.24843/JH.2025.v29.i02.p08, 2025)
This current study is intended to: (1) describe the morphological system of the Balinese banana-related lexicon in Karangasem Regency; (2) analyze its syntactical functions; and (3) describe how colors symbolizing gods determine the use of bananas using the morphological and syntactical theories. The data was obtained from written and oral sources through observation and interview methods, analyzed using distributional method, and its analysis is formally and informally presented. The result of the study shows that: 1) the morphological system of the Balinese banana-related lexicon is categorized into noun, verb, adjective, and derived form resulting from affixational process, reduplication, and asyntactic compound; 2) syntactically, it functions as subject, predicate, object, complement, and adverb; the lexical items referring to the types of bananas  total 21; and 3) four banana colors symbolize gods.